Social psychology - Aronson, Elliot 1932-; Wilson, Timothy D.; Sommers, Samuel R.; Page-Gold, Elizabeth; Lewis, Neil (Pearson, 2022)
"(...) edition of Aronson et al.'s Social Psychology continues a decades-long legacy of accessible and narrative-driven exploration of cutting-edge scientific research. The revised edition brings this engaging sensibility to the review of classic and emerging findings in the field, and focuses a social psychological lens on contemporary developments in the world, including the COVID-19 pandemic, the ubiquity of web-based classrooms and workplaces, sobering spikes in racial violence, and political upheaval in the United States. The xy edition also welcomes to the author team Elizabeth Page-Gould and Neil Lewis, Jr., two social psychologists who have followed the lead of Elliot Aronson by devoting their research careers to the study of pressing societal issues such as intergroup relations and racial inequity"--
Keywords: Social psychology; Psychologie sociale; social psychology; Lehrbuch